Synthesis and characterization of magnetic molecularly imprinted polymers for the rapid and selective determination of clofazimine in blood plasma samples - Zamruddin, Nur Masyithah; Herman, Herman; Asman, Saliza; Nur Hasanah, Aliya (Ce Press, 2024)
Clofazimine (CLF) is a riminophenazine derivative and a new therapeutic option with high efficacy for patients with rifampicin-resistant tuberculosis (TB). The blood levels of CLF are low and suboptimal, so therapeutic drug monitoring is required. Prior to this study, there were no molecular imprinting–based solid phase extraction (SPE) sorbents that could be used to determine the blood CLF levels. Hence, we prepared a magnetic molecularly imprinted polymer (MMIPs) to capture CLF. We employed computational selection of a functional monomer and crosslinker and confirmed these selections based on the association constant (Ka) and a Job plot. We synthesised MMIPs with two surface modifiers and characterized the polymers. Our computational analysis based on the bond energy revealed that methyl methacrylate (MMA) was the most suitable functional monomer at a CLF-to-MMA molar ratio of 1:4. Based on the bond energy, the most suitable crosslinker was trimethylolpropane trimethacrylate (TRIM) at a CLF-to-TRIM molar ratio of 1:1. We determined the Ka of MMA and TRIM in different solvents. Isopropanol produced the highest Ka. The Job plot showed that a template-to-MMA-to-TRIM molar ratio of 1:4:20 was optimal to synthesize imprinted polymer in isopropanol. We prepared MMIPs using two different modifiers, namely aminopropyltrimethoxysilane (APTES) and oleic acid (OA), using the ratio determined from the Job plot. Physical characteristic tests carried out using FT-IR, SEM-EDS, PSA, BET and VSM, showed that the synthesis was success with a spherical and uniform agglomeration of particles, also a flat surface with many holes with a particle size of MMIP-APTES and MMIP-OA respectively 0.14 μm and 0.28 μm, showed a surface area for MMIP-APTES is 2874.51 m2 /g and MMIP-OA 2913.07 m2 /g, exhibiting superparamagnetic properties with a saturation magnetization value of MMIP-APTES 21.1 emu/g− 1 and MMIP-OA 49.9 emu/g− 1 . Adsorption capacity result showed that MMIP-OA fits well with the Langmuir model, while MMIP-APTES fits better with the Freundlich. Application of MMIP-SPE (Magnetic Molecular Imprinted Polymer-Solid Phase Extraction) APTES resulted 92.3 ± 6.1 % and MMIP-SPE-OA 51.5 ± 8.1 % for recovering CLF in blood. The result of selectivity test also showed that MMIP-SPE-APTES is better than MMIP-SPE-OA and selectively recover CLF from human blood plasma existed together with other TB-Drugs. The study result shows that MMIPs with APTES modification can be used for CLF determination in human blood plasma.